To multiply \(-1 \frac{1}{6}\) by \(7\), we first convert the mixed number \(-1 \frac{1}{6}\) into an improper fraction.
-
Convert \(-1 \frac{1}{6}\) to an improper fraction: \[ -1 \frac{1}{6} = -\left(1 \times 6 + 1\right)/6 = -\frac{7}{6} \]
-
Now multiply by \(7\): \[ -\frac{7}{6} \times 7 = -\frac{7 \times 7}{6} = -\frac{49}{6} \]
-
Next, convert \(-\frac{49}{6}\) back to a mixed number:
- Divide \(49\) by \(6\): \[ 49 \div 6 = 8 \quad \text{(with a remainder of } 1\text{)} \]
- So, we have \(8\) as the whole number and the remainder \(1\) gives us \(1/6\).
Thus, \(-\frac{49}{6} = -8 \frac{1}{6}\).
Therefore, the answer is: \[ -\mathbf{8 \frac{1}{6}} \]